2008
DOI: 10.1002/mnfr.200700137
|View full text |Cite
|
Sign up to set email alerts
|

Flavan‐3‐ols: Nature, occurrence and biological activity

Abstract: Representing the most common flavonoid consumed in the American diet, the flavan-3-ols and their polymeric condensation products, the proanthocyanidins, are regarded as functional ingredients in various beverages, whole and processed foods, herbal remedies and supplements. Their presence in food affects food quality parameters such as astringency, bitterness, sourness, sweetness, salivary viscosity, aroma, and color formation. The ability of flavan-3-ols to aid food functionality has also been established in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
491
1
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 655 publications
(513 citation statements)
references
References 227 publications
2
491
1
8
Order By: Relevance
“…7 (Aron and Kennedy, 2008). The blueberry mDP range is similar to polymer lengths reported for apple fruits (3-13; Sanoner et al, 1999;Hamauzu et al, 2005) and grape seeds (3-9; Kennedy et al, 2000;Downey et al, 2003).…”
Section: Pa Subunit Composition Reflects Biosynthetic Gene Expressionsupporting
confidence: 74%
“…7 (Aron and Kennedy, 2008). The blueberry mDP range is similar to polymer lengths reported for apple fruits (3-13; Sanoner et al, 1999;Hamauzu et al, 2005) and grape seeds (3-9; Kennedy et al, 2000;Downey et al, 2003).…”
Section: Pa Subunit Composition Reflects Biosynthetic Gene Expressionsupporting
confidence: 74%
“…Diet is of great importance to human health (44)(45)(46)(47) . The prevention of CVD is attributed to a diversity of effects such as antioxidative (48) , antithrombotic and anti-inflammatory properties, activation of endothelial nitric oxide synthase and inhibition of LDL oxidation (49)(50)(51)(52)(53) . Flavonoids, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Kaulmann et al (2014) reported the polyphenolic profiles of 27 samples of Brassica oleracea varieties and eleven polyphenols were identified. In this study, nine polyphenolic compounds that have been detected or searched in similar matrices, such as caper flowers (Conforti et al, 2011), other edible plants and berries (Gull, Anwar, Sultana, Cervantes Alcayde, & Nouman, 2015;Miean & Mohamed, 2001;Häkkinen, Kärenlampi, Heinonen, Mykkänen, & Törrönen, 1999) and processed vegetables (Aron & Kennedy, 2008), were investigated, but only five compounds were identified and analysed for their concentration in our samples ( Table 2). …”
Section: Analysis Of Polyphenols In Caper Berriesmentioning
confidence: 99%